Chronic Hypertension and Adverse Pregnancy Outcome: A Cohort Study. Issue 1 (January 2018) - Panaitescu, A. M.; Syngelaki, A.; Prodan, N.; Akolekar, R.; Nicolaides, K. H.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2017;50:228–235) There is substantial evidence that chronic hypertension (CH) is associated with adverse pregnancy outcomes. Although meta-analyses of studies examining this issue have been previously conducted, confounding factors and heterogeneity between included studies weaken their impact.